THE CHARACTER OF PSYCHOLOGICAL FEATURES AND ADAPTABILITY TO THE DISEASE IN ADOLESCENTS WITH OSTEOARTHROSIS - Lebets, I.S.; Letyago, A.V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
Psychological features and regulatory systems activity have been studied in adolescents with OA which developed against the background of hypermobility syndrome (main grope) and in patients with hypermobility syndrome without any signs of osteoarthrosis (comparison group). It has been established that in the main group some “pure” types of attitude to the disease, mainly of “adaptive block”, as well as emotional instability and mean level of stress are more frequent. In the comparison group “mixed” types of attitude to the disease and a high level of emotional stress are registered. The level of regulatory systems activity did not differ among the groups of adolescents but with an increase of osteoarthrosis duration it decreased testifying to formation of gradual adaptability to the disease.